(3Gdbhi GdHTQjI aj GdeUGQa GdGSdGejI (B:s (3Hjf GdhGbY h GdeKGdjI (B/s - (3GQTjO, eMehO YHO GdcQjes ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2010)
(3GOQI Gdbhi GdHTQjI h GdeHGOF GdMGceI dgG aj GdUjQI GdGSdGejI , JfejI Gdbhi GdHTQjI h CfTWI GdYGedjf GdGOGQjjf aj GdeUQa GdGSdGej h GNJjGQ GdYGedjf h GdeTGcd GdJj JhGLgge aj gPg GdeUGQa , CNdGbjGJ GdYGedjf aj GdeUGQa GdGSdGejIs
(3edGMb U(B.179s
Keywords: (3EOGQI GdCaQGOs; (3GdHfhc GdGSdGejIs; (3GdHfhc GdGSdGejI ` Gdbhi GdYGedIs